Bioinformatic Analysis of the Genetic Mechanism of Biomineralization of Biogenic Magnetic Nanoparticles in Bacteria Capable of Tumor-Specific Accumulation - Gorobets, Svitlana; Gorobets, Oksana; Kovalova, Svitlana (Innovative Biosystems and Bioengineering, 2022)
Background. Current methods of targeted cancer therapy are not always effective enough and can lead to side effects, such as an increased risk of autoimmune diseases. It is known that some bacteria are capable of specific accumulation in malignant tumors, and therefore can be used as an alternative means of targeted drug delivery. However, the genetic mechanism of tumor-specific accumulation of bacteria is not fully understood and needs to be studied in more detail. Objective. This work aims to identify, by methods of comparative genomics methods, magnetically controlled bacteria among those for which tumor-specific accumulation has already been experimentally shown. Methods. To identify magnetically controlled bacterial strains, i.e., bacteria that biomineralize biogenic magnetic nanoparticles (BMN), the method of comparative genomics was used, namely: pairwise alignment of proteomes with amino acid sequences of Mam-proteins of required for biomineralization of BMN in magnetotactic bacteria Magnetospirillum gryphiswaldense MSR-1. Sequence alignments were performed in the BLAST program of the US National Center for Biotechnology Information (NCBI). Results. The conducted bioinformatic analysis showed that strains of bacteria in which the ability to accumulate specifically in tumors has been experimentally proven are potential producers of BMN of different types. Among them there are potential producers of intracellular crystalline BMN, potential producers of intracellular amorphous BMN, and extracellular crystalline BMN Conclusions. It is expedient to use bacteria-producing BMN as gene vectors and systems of targeted drug delivery to tumors that biomineralize BMN.